GUEST EDITORIAL - Roy, Roger (Zootaxa, 2014)
It is evidently due to my status as the eldest active praying mantid taxonomist that I have been given the honor to introduce this special issue of Zootaxa. Entirely devoted to the study of Mantodea, and planned by Julio Rivera, this volume constitutes a significant initiative; it responds to a renewed research interest in praying mantids and gives these insects their deserved recognition.